2019
DOI: 10.1016/j.heliyon.2019.e02033
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein serum levels related to metabolic syndrome in patients with schizophrenia

Abstract: Background Schizophrenia is associated with a lowered life expectancy due to cardiovascular disease. This is, at least in part, related to an increased vulnerability to the development of metabolic syndrome (MetS) in patients with schizophrenia. The dysregulation of apolipoproteins (Apos) may also play a role in the pathogenesis of schizophrenia via their effect on cerebral cholesterol processing. Aim The aim of this study was to investigate serum Apos A1, C3, E, A2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 39 publications
0
37
0
1
Order By: Relevance
“…In a previous paper, we observed that apolipoprotein A2 was lower in patients with schizophrenia without MetS, unlike patients with MetS [ 48 ]. Apolipoprotein A2 is the second most abundant protein in high-density lipoproteins and has potent anti-inflammatory effects [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous paper, we observed that apolipoprotein A2 was lower in patients with schizophrenia without MetS, unlike patients with MetS [ 48 ]. Apolipoprotein A2 is the second most abundant protein in high-density lipoproteins and has potent anti-inflammatory effects [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria, criteria for MetS and clinical assessments are described in a previous paper. 14 We included 110 patients with the diagnosis of paranoid schizophrenia verified according to the International Statistical Classification of Diseases, 10th Revision (ICD-10: F20) and who were suffering from an acute relapse. Patients have been divided into groups according to criteria of the International Diabetes Federation (IDF, 2005): 42 patients with MetS and 68 patients without MetS.…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
“…Based on a study on apo levels that showed significant differences of apoA2 and apoC levels in metabolic syndrome, 37 a population sample size of 38 patients was calculated, giving 80% power to detect a difference with a two-sided alpha error of 0.05 (nQuery, Statsol, USA). Descriptive statistics and means±SDs were calculated for all continuous variables in the study.…”
Section: Methodsmentioning
confidence: 99%